KEBERADAAN FUNGI SELULOLITIK PADA TANAH BEKAS ERUPSI GUNUNG SINABUNG DI KABUPATEN KARO - Dendi Parasian Pane; Deni Elfiati; Delvian Delvian (Program studi Kehutanan USU, 2016)
Volcanic dust expelled while eruption have a sour potential of hydrogen and the result led to a decrease in the diversity various and microorganism population. The fungi are important instrument in the process of decomposition of organic material for all types of soil. The fungi selulolitic have the ability to hydrolyze the cellulose naturally through it’s cellulose activity. This research aims to study the presence of selulolitic fungi contained on land under forest stands are former eruption of Sinabung Mountain in Karo District. Soil sampling was done with diagonally composite. Soil samples exposed to the eruption consisted of two samples that volcanic dust with a depth of 0-5 cm and mixed with volcanic dust soil to a depth of 5-20 cm, while for the control of soil samples consisted of a sample of the soil to a depth of 0-20 cm. The isolation of fungi and identification were done in the laboratory of Soil Biology, Agroecotechnology, Faculty of Agriculture, University of Sumatera Utara. This research was carried out from March 2015 until May 2015. The results showed that there were 4 types of selulolitic fungi found in soil samples affected by volcanic dust and are not affected by volcanic dust, namely Aspergillus, Penicillium, Rhizopus, and Trichoderma.Keywords : volcanic dust, former eruption land, cellulose, selulolitic fungi